The Relationship Between Fasting Blood Glucose Levels and Creatinine Levels in Patients with Type 2 Diabetes Mellitus Based on Duration of Disease** *(An Explanatory Case Study at dr. Doris Sylvanus Regional General Hospital, Palangka Raya City, January: HUBUNGAN KADAR GLUKOSA DARAH PUASA DENGAN KADAR KREATININ PASIEN DIABETES MELLITUS TIPE 2 BERDASARKAN LAMA MENDERITA (Studi Kasus Eksplanatif Di RSUD dr. Doris Sylvanus Kota Palangka Raya Periode Januari 2023 – Desember 2024) - Veronica, Veronica (Barigas: Medical and Health Science Journal, 2026)
Type 2 diabetes mellitus is a metabolic disease characterized by high blood glucose levels (hyperglycemia) due to insufficient insulin secretion or reduced inulin activity, with the number of patients increasing annually. Fasting blood glucose (FBS) is one of the tests used to monitor blood glucose levels, while creatinine levels are used to assess renal function in patients with diabetic nephropathy or renal complications in type 2 diabetes mellitus (DM2). Based on this, this study was conducted to determine whether fasting blood glucose is associated with creatinine levels in patients with type 2 diabetes mellitus. To determine whether there is a relationship between fasting blood glucose and creatinine levels. This is an explanatory case study using the Spearman rank test for non-normally distributed data. The results of the Spearman rank test showed that from the characteristics of the patients, there were 98 patients with type 2 diabetes mellitus with diabetic nephropathy complications, 45.9% of patients were male and 54.1% of patients were female with the recorded patient ages being 1.0% of patients (20-29 years), 1.0% of patients (30-39 years), 7.1% of patients (40-49 years), 39.8% of patients (50-59), 41.8% of patients (60-69 years), 9.2% of patients (≥70 years). And also from 98 patients with type 2 diabetes mellitus based on the length of diagnosis there were 18.4% (1-5 years), 45.9% (6-10 years), 35.7% (>10 years). That there was no relationship between fasting blood glucose and creatinine levels because the significance value was 0.830 (sig> 0.05). There is no relationship between fasting blood glucose and creatinine levels in patients with type 2 diabetes mellitus at Dr. Doris Sylvanus Regional General Hospital, Palangka Raya City. Keywords: Type 2 diabetes mellitus, Spearman test, fasting blood glucose, creatinine levels, Dr. Doris Sylvanus Regional General Hospital, Palangka Raya City